The new sort of winter barley for Dagestan conditions - B. A. Batasheva (Юг России: экология, развитие)
The work was done on the Dagestan experimental station VIR by N.I.Vavilov in 1984-2001.The new sort of winter barley Dagestanskiy zolotistiy was founded by the method of individual selection. The sort was entered in the State list(2001) and admited to cultivate on the sixth region.